Electrically-assisted slow-release antibacterial conductive ultrafiltration membrane as well as preparation method and application thereof

By blending hollow mesoporous nanocarbon spheres and aminolated multi-walled carbon nanotubes with antibacterial agents in the ultrafiltration membrane, an electrically assisted sustained release antibacterial conductive ultrafiltration membrane was constructed, which solved the problems of short service life of the existing ultrafiltration membrane under biological contamination and limited application fields, and achieved efficient antibacterial and screening performance, significantly improving the antifouling and antibacterial properties of the membrane.

CN119680396APending Publication Date: 2025-03-25天冀桢材科技(河北)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411910113.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

Smart Images

  • Figure CN119680396A_ABST
    Figure CN119680396A_ABST
Patent Text Reader

Abstract

The invention discloses an electricity-assisted slow-release antibacterial conductive ultrafiltration membrane and a preparation method and application thereof, and belongs to the technical field of sewage treatment, the electricity-assisted slow-release antibacterial conductive ultrafiltration membrane comprises a matrix, an antibacterial filler and a conductive filler, the matrix is polyether sulfone, the antibacterial filler is hollow mesoporous carbon spheres loaded with broad-spectrum bactericide povidone iodine, and the conductive filler is an aminated carbon nanotube; the preparation method comprises the following steps: S1, synthesizing hollow mesoporous carbon spheres by adopting a template method; s2, immersing the hollow mesoporous carbon spheres into a povidone iodine solution for adsorption to obtain hollow nano carbon spheres loaded with an antibacterial agent; s3, adopting an impregnation phase conversion technology, and adding antibacterial filler-povidone iodine loaded hollow mesoporous carbon spheres and conductive filler-aminated carbon nanotubes into the membrane casting solution to successfully construct the slow-release antibacterial composite conductive ultrafiltration membrane. The antibacterial slow-release nano material and the conductive nano material are organically combined with the ultrafiltration membrane, so that the screening performance and the anti-pollution performance of the ultrafiltration membrane are improved, and the biological pollution of the membrane and the loss of an antibacterial agent are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage separation, and in particular to an electrically assisted slow-release antibacterial conductive ultrafiltration membrane and a preparation method and application thereof. Background Art

[0002] The United Nations emphasizes that water quality is threatened by pollution. More than 90% of untreated domestic sewage and 70% of untreated industrial waste are discharged into surface water every day, causing irreversible impacts on water resources, human health and biodiversity. Membrane separation technology has become an effective solution to water pollution. However, the practical application of membrane separation is often hindered by the presence of minerals, organic matter and microbial contamination in domestic and industrial wastewater. Among these pollutants, biological contamination has become a major challenge affecting the screening performance and service life of separation membranes. The sources of biological contamination mainly include bacteria, viruses, protozoa, parasitic worms and algae in sewage. These microorganisms will grow and reproduce rapidly in the water environment, thereby affecting the water quality, posing a serious threat to the health of animals, plants and even humans. The extracellular polymers released by these microorganisms adhere to each other and tightly adhere to the surface of the separation membrane. This will seriously block the water flow channel, increase the permeation resistance of water during water treatment, cause a decrease in water flux, accelerate the aging of the separation membrane, and increase operating costs. Commonly used biofouling control strategies include feed water pretreatment, membrane cleaning and membrane modification. Since membrane modification can reduce the cost of pretreatment and membrane cleaning, it has been actively studied by scholars. Considering that hydrophilic modification can effectively reduce the attachment of bacterial cells to the cell membrane, it cannot remove or inactivate the attached cells. Therefore, biofilms are still formed in long-term operation. Therefore, giving separation membranes self-cleaning and antibacterial properties to enhance the sustainability and economy of the separation process is a hot topic for scholars.

[0003] Scholars often add antimicrobial materials to separation membranes to effectively manage biofouling. Research results show that these antimicrobial membranes exhibit effective antimicrobial activity against both Staphylococcus aureus and Escherichia coli. Therefore, imparting antimicrobial properties to separation and optimizing the overall structure of ultrafiltration membranes bring new possibilities to water treatment and membrane separation technology.

[0004] Povidone-iodine is a complex product of polyvinylpyrrolidone and iodine, known for its chemical stability, low toxicity and high bactericidal activity. It can provide affinity to bacterial membranes through surfactants, bind the iodine it carries to cell membranes and cytoplasm, and use the super strong oxidizing property of free iodine to oxidize or iodinate sulfhydryl compounds, peptides, proteins, enzymes, lipids, etc., thereby achieving the purpose of sterilization and disinfection. It has a broad spectrum of antibacterial properties and shows outstanding effects on common fungi and viruses. However, high-intensity sunlight exposure can cause I 3-The decomposition of iodine acts as a sustained-release reservoir of iodine, reducing the bactericidal ability of the povidone-iodine system. Therefore, scholars have considered externally coated sustained-release materials. Sustained-release systems usually include liposomes, microspheres and microcapsules, nanoparticles, emulsions, hydrogels, membranes, etc. The drug release process and mechanism of different drug sustained-release systems are different, which is mainly affected by the internal structure of the material.

[0005] Therefore, we urgently need to construct a new conductive ultrafiltration membrane with electrically assisted sustained-release antibacterial properties, which has excellent basic screening performance, significant antifouling performance and lasting antibacterial performance under the influence of electric field, and can also sustainably release antibacterial agents, providing a basis for the future promotion and widespread application of nano sustained-release antibacterial agents in water purification and recycling. Summary of the invention

[0006] To this end, the present invention provides an electrically assisted slow-release antibacterial conductive ultrafiltration membrane and a preparation method and application thereof, so as to solve the problems of short service life and limited application fields of ultrafiltration membranes caused by biological contamination in the prior art.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] According to a first aspect of the present invention, there is provided a method for preparing an electrically assisted sustained-release antibacterial conductive ultrafiltration membrane, comprising the following steps:

[0009] S1. First, a nano-silica template is prepared by a sol-gel method. Tetraethyl orthosilicate is used as a silica precursor and is added dropwise to a mixed solution of ethanol, deionized water and ammonia water in a volume ratio of 26:1:3. The mixture is mixed and stirred to obtain silica microspheres. Subsequently, the silica is modified with 3-aminopropyltriethoxysilane and then transferred to a sucrose solution for a hydrothermal reaction. Finally, after sintering in a tubular furnace, the silica template is etched with a solution prepared with lithium fluoride and hydrochloric acid to obtain hollow mesoporous carbon spheres.

[0010] S2. placing the hollow mesoporous carbon spheres prepared in S1 in a povidone-iodine solution for continuous reaction; subsequently, removing free iodine using n-heptane, and drying the resulting product to obtain hollow mesoporous nanocarbon spheres loaded with an antibacterial agent;

[0011] S3. The hollow mesoporous nanocarbon spheres loaded with antibacterial agents prepared in S2 and the amino-modified multi-walled carbon nanotubes are added to the casting solution in a ratio of (1-2): (1-2), and a slow-release antibacterial composite conductive ultrafiltration membrane is prepared by an immersion phase inversion method.

[0012] Furthermore, in S3, the casting solution includes the following components:

[0013] N,N-dimethylacetamide (76 wt.%), polyvinylpyrrolidone (5 wt.%) and polyethersulfone (19 wt.%).

[0014] Furthermore, in the S1, the amount of ethyl orthosilicate added is 10-50 mL, the amount of 3-aminopropyltriethoxysilane added is 0-10 mL, the concentration of sucrose is 0.1-0.9 mol / L, the hydrothermal temperature is 100-200°C, and the firing temperature of the carbon balls is 500-1000°C.

[0015] Furthermore, tetraethyl orthosilicate ≥98%; lithium fluoride ≥99%; hydrochloric acid ≥36%; outer diameter of amino-modified multi-walled carbon nanotubes: 8-15nm, length: 50μm; n-heptane ≥98%; ammonia water, AR, 25-28%; sucrose is AR grade powder.

[0016] Furthermore, in S2, the concentration of the povidone-iodine solution is 1-10 g / L, and the reaction time is 5-20 h.

[0017] Furthermore, in S3, the amount of hollow mesoporous carbon nanospheres loaded with antibacterial agents added to the casting solution is 0.1-0.5 g, and the amount of amino-modified multi-walled carbon nanotubes is 0-0.5 g.

[0018] Furthermore, in S3, the reaction temperature of the casting solution is 50-100° C., and the reaction time is 1-12 h.

[0019] Furthermore, the polyethersulfone M w =62 kDa, and the polyvinyl pyrrolidone is polyvinyl pyrrolidone K-30.

[0020] According to a second aspect of the present invention, an electrically assisted sustained-release antibacterial conductive ultrafiltration membrane is provided, which is prepared by the method as described above, wherein the ultrafiltration membrane comprises a matrix, an antibacterial filler and a conductive filler, wherein the matrix is ​​polyethersulfone (PES), and the antibacterial filler is a hollow mesoporous carbon sphere (C PVP-I ), the conductive filler is amino-modified multi-walled carbon nanotubes (CNTs-NH2).

[0021] According to a third aspect of the present invention, there is provided an application of an electrically assisted slow-release antibacterial conductive ultrafiltration membrane in wastewater separation and purification, which is prepared by the above method.

[0022] The present invention has the following advantages:

[0023] 1. This application constructs a new type of nano antibacterial agent by loading a broad-spectrum antibacterial agent, povidone iodine, into hollow mesoporous carbon spheres. 3- Decomposition reduces the bactericidal ability of povidone iodine. Therefore, the antibacterial rate of the composite film constructed based on this new type of nano antibacterial agent can reach more than 95%. And before the antibacterial performance test, the antibacterial rate of the composite antibacterial film after being placed for 30 days still remains above 40%.

[0024] 2. The present application blends a three-dimensional network of hollow mesoporous nanocarbon spheres loaded with antibacterial agents and amino multi-walled carbon nanotubes in a polyethersulfone matrix to construct a composite ultrafiltration membrane with excellent antifouling and conductive properties, and the surface resistance of the composite membrane is reduced to 12.36 kΩ / sq. On the other hand, the flux loss of the composite membrane is not less than 70% under a long-term antifouling test of 11 hours, showing stable and excellent separation performance.

[0025] 3. The present application exhibits antibacterial properties under electrical assistance. Under the application of an electric field, the conductive network triggers the hollow mesoporous nanospheres loaded with antibacterial agents to release effective iodine (approximately 1.99 times the spontaneous release).

[0026] 4. The electrically assisted membrane pool constructed in this application can significantly improve the screening performance of the composite conductive separation membrane under the assistance of the electric field. The interception rate of Congo red and methyl blue dyes of the composite membrane is higher than 98%, showing excellent dye screening performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0028] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0029] Figure 1 A schematic diagram of the structure and membrane pool composition of the electrically assisted slow-release antibacterial conductive ultrafiltration membrane provided by the present invention;

[0030] Figure 2 A graph showing the test results of electrically assisted Congo red and methyl blue dye sieving of different conductive ultrafiltration membranes provided by the present invention;

[0031] Figure 3 A graph showing the test results of the electrically triggered antibacterial agent sustained release of different conductive ultrafiltration membranes provided by the present invention;

[0032] Figure 4 A schematic diagram showing a comparison of the antibacterial rates of Escherichia coli of different conductive ultrafiltration membranes provided by the present invention;

[0033] Figure 5A diagram showing the antibacterial effect of different conductive ultrafiltration membranes provided by the present invention on Escherichia coli. DETAILED DESCRIPTION

[0034] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Mesoporous carbon spheres are new materials with regular spherical shapes. They have the advantages of large specific surface area, high chemical stability, good biocompatibility, easy surface modification and high drug loading. Combined with the design of stimuli response and targeting functions, they can prevent premature release of transported drugs and deliver drugs in a targeted manner. They have great application prospects in the fields of biomedicine, energy storage, environmental governance and catalysis. Commonly used response stimuli include light, pH, ultrasound, temperature and electricity. Compared with other technologies, electrical response can be more adaptable to water environments and has cost advantages. When combined with stimuli response design, targeting function and other functions, hollow mesoporous carbon spheres can effectively prevent premature drug release and promote targeted drug delivery, which makes them have broad application prospects in biomedicine, energy storage, environmental treatment and catalysis. In order to enhance the electrical properties of the membrane, conductive fillers such as carbon nanotubes are considered. The effective use of carbon nanotubes in composite applications depends on the ability of carbon nanotubes to be evenly dispersed throughout the matrix and the compatibility between carbon nanotubes and the matrix. The main problem with using raw carbon nanotubes is their insolubility in solvents and their weak affinity for most polymers. Therefore, surface functionalization was performed to improve its dispersibility and performance. Surface oxidation and hydrophilic functional groups also help carbon nanomaterials to disperse better into relevant matrices. Amine groups have high reactivity and rich chemical properties. Nitrogen doping of carbon nanotubes can not only improve their water dispersibility, thereby solving the disadvantage of carbon nanotubes being difficult to disperse in practical applications, but also improve their water dispersibility.

[0036] The invention provides an electrically assisted sustained-release antibacterial conductive ultrafiltration membrane, comprising a matrix, an antibacterial filler and a conductive filler, wherein the matrix is ​​polyethersulfone (PES), and the antibacterial filler is a hollow mesoporous carbon sphere (C 606) loaded with a broad-spectrum bactericide, povidone iodine. PVP-I ), the conductive filler is amino-modified multi-walled carbon nanotubes (CNTs-NH2).

[0037] The present invention also provides a method for preparing an electrically assisted slow-release antibacterial conductive ultrafiltration membrane, comprising the following steps:

[0038] S1. A nanoscale spherical silica (SiO2) template was prepared using a sol-gel method. Tetraethyl orthosilicate (TEOS) was added to a mixed solution of ethanol, deionized water and ammonia water to obtain a silica (SiO2) microsphere template. Silica microspheres (SiO2) were modified using 3-aminopropyltriethoxysilane (APTES), and then uniformly dispersed in a sucrose aqueous solution for a hydrothermal reaction. The polysaccharide-coated silica template was then placed in a tubular furnace and carbonized under an argon atmosphere. Finally, the silica template was etched using a hydrofluoric acid solution prepared using lithium fluoride (LiF) and hydrochloric acid (HCl) to obtain hollow mesoporous nanocarbon spheres (HMCS).

[0039] S2. The hollow mesoporous carbon spheres (HMCS) prepared in S1 are placed in a povidone-iodine (PVP-I) solution and reacted continuously. Subsequently, free iodine is removed using n-heptane, and the resulting product is dried to obtain hollow mesoporous carbon spheres (C PVP-I ).

[0040] S3. The hollow mesoporous nanospheres loaded with antibacterial agents prepared in S2 (C PVP-I ) and aminated multi-walled carbon nanotubes (CNTs-NH2) were uniformly dispersed in the casting solution, and the slow-release antibacterial composite conductive ultrafiltration membrane was prepared by using the impregnation phase conversion technology; different addition amounts of aminated multi-walled carbon nanotubes (CNTs-NH2) and hollow mesoporous nanospheres loaded with antibacterial agents (C PVP-I ) is introduced into N, N-dimethylacetamide (DMAc) solution for ultrasonic dispersion. Subsequently, the mixture is mixed with pre-dried polyvinyl pyrrolidone (PVP) and polyether sulfone (PES) powders, and continuously heated and stirred. The solution is cast onto a glass plate using a glass rod, and a flat film is formed by pouring. After standing and leveling, the glass plate is quickly immersed in water to induce phase change to construct a slow-release antibacterial conductive ultrafiltration membrane.

[0041] Specifically, in S1, the amount of tetraethyl orthosilicate (TEOS) added is 0-50 mL, the amount of 3-aminopropyltriethoxysilane (APTES) added is 0-10 mL, and the amount of sucrose (C 12 H 22 O 11 )The concentration of the aqueous solution is 0.1-0.9 mol / L.

[0042] Specifically, tetraethyl orthosilicate (TEOS) ≥ 98%, ammonia water (NH4OH) ≥ 99%, hydrochloric acid (HCl) ≥ 36%, n-heptane (n-Heptane) ≥ 98%, and ethanol (C2H5OH) ≥ 98%.

[0043] Lithium fluoride (LiF) and sucrose (C 12 H 22 O 11) is AR grade powder.

[0044] Specifically, in S1, the hydrothermal reaction temperature is 150-200°C.

[0045] Specifically, in S1, the reaction temperature in the tube furnace is 500-1000°C.

[0046] Specifically, in S1, the reaction time of etching the silica template with the hydrofluoric acid solution is 0-10 hours.

[0047] Specifically, in S2, the concentration of the povidone-iodine (PVP-I) solution is 1-10 g / L.

[0048] Specifically, in S2, the reaction time is 5-20 hours.

[0049] Specifically, in S3, hollow mesoporous nanospheres (C PVP-I ) is 0-0.5g, and the amount of amino-modified multi-walled carbon nanotubes (CNTs-NH2) is 0-0.5g.

[0050] Specifically, in S3, the reaction temperature of the casting solution is 50-100° C. and the reaction time is 0-12 h.

[0051] In order to better illustrate the antibacterial effect of the ultrafiltration membrane prepared by the technical solution of the present application, the following examples are provided for illustration.

[0052] Example 1

[0053] This embodiment provides a method for preparing an electrically assisted sustained-release antibacterial conductive ultrafiltration membrane, comprising the following steps:

[0054] S1. Preparation of nano-scale spherical silica templates using the sol-gel method. 10 mL of tetraethyl orthosilicate was added to a mixed solution consisting of 520 mL of ethanol, 20 mL of deionized water and 60 mL of ammonium hydroxide, and the silica microsphere template was obtained by stirring at 30 ° C for 3 h. 10 mL of 3-aminopropyltriethoxysilane was used to modify the silica microspheres, and the reaction was continued at 70 ° C for 36 h. Then, it was evenly dispersed in a 0.1 mol / L sucrose aqueous solution and subjected to a hydrothermal reaction at 150 ° C for 3 h. The polysaccharide-coated silica template was then placed in a tubular furnace and carbonized at 500 ° C for 3 h under an argon atmosphere. Finally, the hollow mesoporous carbon spheres prepared using lithium fluoride (2 g) and hydrochloric acid (20 mL) were placed in a 1 g / L povidone-iodine solution and reacted continuously for 5 h. Subsequently, the free iodine was removed by washing with n-heptane, and the resulting product was dried to obtain hollow mesoporous carbon spheres loaded with a broad-spectrum antibacterial agent.

[0055] S3. The hollow mesoporous nanocarbon spheres and amino multi-walled carbon nanotubes loaded with antibacterial agents prepared in S2 are uniformly dispersed in the casting solution, and the slow-release antibacterial composite conductive ultrafiltration membrane is prepared by immersion phase conversion technology. Specifically, 2:1 amino multi-walled carbon nanotubes and hollow mesoporous nanocarbon spheres loaded with antibacterial agents are introduced into N, N-dimethylacetamide (76wt.%) solution and ultrasonically dispersed at 180W power for 1h. Subsequently, the mixture is mixed with pre-dried polyvinyl pyrrolidone (5wt.%) and polyether sulfone (19wt.%) powders. By continuous heating and stirring at 50°C for 5h. The casting solution is poured onto a glass plate and scraped using a 200μm scraping rod to form a flat film by pouring. After standing and leveling, the glass plate is quickly immersed in water to induce phase change, thereby obtaining an electrically assisted slow-release antibacterial ultrafiltration membrane. In order to ensure complete phase change and eliminate unreacted polyvinyl pyrrolidone molecules, the water is changed every 12 hours.

[0056] Example 2

[0057] This embodiment provides a method for preparing an electrically assisted sustained-release antibacterial conductive ultrafiltration membrane, comprising the following steps:

[0058] S1. Preparation of nano-scale spherical silica templates using the sol-gel method. 20 mL of tetraethyl orthosilicate was added to a mixed solution consisting of 520 mL of ethanol, 20 mL of deionized water, and 60 mL of ammonium hydroxide, and stirred at 30 ° C for 3 h to obtain a silica microsphere template. 8 mL of 3-aminopropyltriethoxysilane was used to modify silica, and the reaction was continued at 70 ° C for 36 h. Then, it was evenly dispersed in a 0.5 mol / L sucrose aqueous solution and subjected to a hydrothermal reaction at 190 ° C for 3 h. The polysaccharide-coated silica template was then placed in a tubular furnace and carbonized at 900 ° C for 3 h under an argon atmosphere. Finally, the silica template was etched for 2 h using a hydrofluoric acid solution prepared with lithium fluoride (2 g) and hydrochloric acid (20 mL) to obtain hollow mesoporous carbon spheres.

[0059] S2. The hollow mesoporous carbon spheres prepared in S1 are placed in a 10 g / L povidone-iodine solution and reacted for 10 hours. Subsequently, free iodine is removed by washing with n-heptane, and the obtained product is dried to obtain hollow mesoporous carbon spheres loaded with a broad-spectrum antibacterial agent.

[0060] S3. The hollow mesoporous nanospheres loaded with antibacterial agents and aminated multi-walled carbon nanotubes prepared in S2 are uniformly dispersed in the casting solution, and a slow-release antibacterial composite conductive ultrafiltration membrane is prepared by immersion phase conversion technology. Specifically, a 1:1 aminated multi-walled carbon nanotube and hollow mesoporous nanospheres loaded with antibacterial agents are introduced into N, N-dimethylacetamide (76wt.%) solution and ultrasonically dispersed at 180W power for 1h. Subsequently, the mixture is mixed with pre-dried polyvinyl pyrrolidone (5wt.%) and polyether sulfone (19wt.%) powders. By continuous heating and stirring at 70°C for 6h. The casting solution is poured onto a glass plate and scraped using a 200μm scraping rod to form a flat film by pouring. After standing and leveling, the glass plate is quickly immersed in water to induce phase change, thereby obtaining an electrically assisted slow-release antibacterial ultrafiltration membrane. In order to ensure complete phase change and eliminate unreacted polyvinyl pyrrolidone molecules, the water is changed every 12 hours.

[0061] Example 3

[0062] This embodiment provides a method for preparing an electrically assisted sustained-release antibacterial ultrafiltration membrane, comprising the following steps:

[0063] S1. Preparation of nano-scale spherical silica templates using the sol-gel method. 50 mL of tetraethyl orthosilicate was added to a mixed solution consisting of 520 mL of ethanol, 20 mL of deionized water, and 60 mL of ammonium hydroxide, and stirred at 30 ° C for 3 h to obtain a silica microsphere template. 10 mL of 3-aminopropyltriethoxysilane was used to modify silica, and the reaction was continued at 70 ° C for 36 h. Then, it was evenly dispersed in a 0.6 mol / L sucrose aqueous solution and subjected to a hydrothermal reaction at 180 ° C for 3 h. The polysaccharide-coated silica template was then placed in a tubular furnace and carbonized at 1000 ° C for 3 h under an argon atmosphere. Finally, the silica template was etched for 4 h using a hydrofluoric acid solution prepared with lithium fluoride (2 g) and hydrochloric acid (20 mL) to obtain hollow mesoporous carbon spheres.

[0064] S2. The hollow mesoporous carbon spheres prepared in S1 were placed in a 5 g / L povidone-iodine solution and reacted for 15 hours. Subsequently, free iodine was removed using n-heptane, and the obtained product was dried to obtain hollow mesoporous carbon spheres loaded with a broad-spectrum antibacterial agent.

[0065] S3. The hollow mesoporous nanospheres loaded with antibacterial agents and aminated multi-walled carbon nanotubes prepared in S2 are uniformly dispersed in the casting solution, and the slow-release antibacterial composite conductive ultrafiltration membrane is prepared by immersion phase conversion technology. Specifically, 1:2 aminated multi-walled carbon nanotubes and hollow mesoporous nanospheres loaded with antibacterial agents are introduced into N, N-dimethylacetamide (76wt.%) solution and ultrasonically dispersed at 180W power for 1h. Subsequently, the mixture is mixed with pre-dried polyvinyl pyrrolidone (5wt.%) and polyether sulfone (19wt.%) powders. By continuous heating and stirring at 100°C for 12h. The casting solution is poured onto a glass plate and scraped using a 200μm scraping rod to form a flat film by pouring. After standing and leveling, the glass plate is quickly immersed in water to induce phase change, thereby obtaining an electrically assisted slow-release antibacterial ultrafiltration membrane. In order to ensure complete phase change and eliminate unreacted polyvinyl pyrrolidone molecules, the water is changed every 12 hours.

[0066] At the same time, the ultrafiltration membrane produced by using only polyethersulfone (PES) as the matrix, the ultrafiltration membrane produced by using polyethersulfone (PES) as the matrix and hollow mesoporous carbon spheres (C PVP-I ) as a matrix and an ultrafiltration membrane produced by using polyethersulfone (PES) as a matrix and amino-modified multi-walled carbon nanotubes (CNTs-NH2), respectively, as comparative examples to be compared with the above-mentioned Examples 1-3.

[0067] The finished films prepared in Examples 1 to 3 were tested and the results were as follows: Figure 1-5 As shown:

[0068] Summarize:

[0069] 1. The electrically assisted sustained-release antibacterial ultrafiltration membrane obtained in Examples 1-3 is as follows: Figure 1 As shown in the figure, a new conductive ultrafiltration membrane with electrically assisted slow-release antibacterial properties was developed. This composite membrane uses hollow mesoporous nanocarbon spheres as slow-release carriers, povidone iodine as a drug model, and amino-modified multi-walled carbon nanotubes as conductive fillers. The composite membrane was placed in a homemade electrically assisted membrane pool. The auxiliary electric field not only improved the screening performance of the composite membrane, but also stimulated the composite conductive membrane to release antibacterial agents. This study laid a theoretical foundation for the promotion and widespread application of slow-release antibacterial agents in water recycling.

[0070] 2. Two dyes, methyl blue and Congo red, were used as models to evaluate the dye rejection performance of the composite ultrafiltration membrane. Figure 2As shown, several composite membranes containing aminated multi-walled carbon nanotubes as conductive fillers showed an increase in rejection at both 2V and 3V, with the highest increase being 21.31%. And the retention rates of Congo red and methyl blue dyes were always above 98%. This enhancement can be attributed to the formation of a three-dimensional conductive network within the polyethersulfone matrix by hollow mesoporous carbon nanospheres loaded with antibacterial agents and aminated multi-walled carbon nanotubes, which endow the separation membrane with excellent electrical properties. By increasing the voltage, the composite conductive ultrafiltration membrane can be negatively charged. It may lead to an electrostatic repulsion of the dye molecules in the cake layer, thereby improving the screening performance of the dye.

[0071] 3. Pass Figure 3 The evaluation of the composite ultrafiltration membrane PES / CNT-NH2 / C PVP-I 1:1 release performance of antimicrobial agents at different voltages. The effective iodine content was significantly increased under 2V and 3V electric fields. The hollow mesoporous nanospheres loaded with antimicrobial agents include iodine molecules containing carbonyl bonds, as well as polyiodides produced by ionization and assembly, which interact and bind with iodine molecules through halogen bonds. However, the chemical balance achieved by the complexation-release of effective iodine is easily affected by external factors. When sufficient electric field stimulation is applied, the ionization assembly of iodine molecules in polyiodides is affected, thereby affecting the release of effective iodine to solve the problems associated with effective iodine loss and sensitization susceptibility. This electrically assisted antibacterial ultrafiltration membrane provides a promising strategy to solve membrane fouling problems and enhance the potential of membrane separation applications and markets.

[0072] 4. Pass Figure 4 and Figure 5 It can be seen that the antibacterial and sustained-release properties of hollow mesoporous carbon nanospheres loaded with antibacterial agents are introduced into ultrafiltration membranes to solve the biological contamination problem encountered when developing anti-biofilm materials. Escherichia coli was used as a model strain to evaluate the long-term antibacterial effect of the membrane. Figure 4 The results described in the present study indicate that the membranes containing hollow mesoporous carbon nanospheres loaded with antimicrobial agents exhibited significantly enhanced antibacterial properties. PVP-I / CNT-NH2 1:1 antibacterial rate can reach more than 95%. Composite membrane PES / C PVP-I / CNT-NH2 2:1 showed the most significant effect, reaching an antibacterial rate of 100%. This enhanced efficacy can be attributed to the hollow mesoporous nanocarbon spheres loaded with antimicrobial agents, which disrupted E. coli cell functions by hindering hydrogen bonds and changing the cell membrane structure, resulting in rapid sterilization. In addition, the composite antibacterial membranes were placed for 30 days before the antibacterial performance test to evaluate the long-term antibacterial ability of the membranes. The membrane PES / CPVP-I / CNT-NH2 1:1 also had antibacterial ability after 30 days, with an antibacterial rate of more than 40%. It is well known that iodine preparations are prone to photooxidative decomposition, which affects their antibacterial ability. The assembled hollow mesoporous nanocarbon spheres loaded with antimicrobial agents can effectively inhibit the loss of antibacterial components, and the membrane with the highest content of hollow mesoporous nanocarbon spheres loaded with antimicrobial agents can still maintain an antibacterial ratio of 100% after 30 days. This further affirms the ability of this method to maintain the long-term effectiveness of antimicrobial release.

[0073] Based on the above summary, this application also has the following advantages:

[0074] 1. This application constructs a new type of nano antibacterial agent by loading a broad-spectrum antibacterial agent, povidone iodine, into hollow mesoporous carbon spheres. 3- Decomposition reduces the bactericidal ability of povidone iodine. Therefore, the antibacterial rate of the composite film constructed based on this new type of nano antibacterial agent can reach more than 95%. And before the antibacterial performance test, the antibacterial rate of the composite antibacterial film after being placed for 30 days still remains above 40%.

[0075] 2. The present application blends a three-dimensional network of hollow mesoporous nanocarbon spheres loaded with antibacterial agents and amino multi-walled carbon nanotubes in a polyethersulfone matrix to construct a composite ultrafiltration membrane with excellent antifouling and conductive properties, and the surface resistance of the composite membrane is reduced to 12.36 kΩ / sq. On the other hand, the flux loss of the composite membrane is not less than 70% under a long-term antifouling test of 11 hours, showing stable and excellent separation performance.

[0076] 3. The present application exhibits antibacterial properties with electrical assistance. Under the application of an electric field, the conductive network triggers the hollow mesoporous nanospheres loaded with antibacterial agents to release effective iodine (approximately 1.99 times the spontaneous release).

[0077] 4. The electrically assisted membrane pool constructed in this application can significantly improve the screening performance of the composite conductive separation membrane under the assistance of the electric field. The interception rate of Congo red and methyl blue dyes of the composite membrane is higher than 98%, showing excellent dye screening performance.

[0078] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing an electrically assisted sustained-release antibacterial conductive ultrafiltration membrane, characterized in that: The steps include: S1. First, a nano-silica template is prepared by a sol-gel method. Tetraethyl orthosilicate is used as a silica precursor and is added dropwise to a mixed solution of ethanol, deionized water and ammonia water in a volume ratio of 26:1:

3. The mixture is mixed and stirred to obtain silica microspheres. Subsequently, the silica is modified with 3-aminopropyltriethoxysilane and then transferred to a sucrose solution for a hydrothermal reaction. Finally, after sintering in a tubular furnace, the silica template is etched with a solution prepared with lithium fluoride and hydrochloric acid to obtain hollow mesoporous carbon spheres. S2. placing the hollow mesoporous carbon spheres prepared in S1 in a povidone-iodine solution for continuous reaction; subsequently, removing free iodine using n-heptane, and drying the resulting product to obtain hollow mesoporous nanocarbon spheres loaded with an antibacterial agent; S3. The hollow mesoporous nanocarbon spheres loaded with antibacterial agents prepared in S2 and the amino-modified multi-walled carbon nanotubes are added to the casting solution in a ratio of (1-2): (1-2), and a slow-release antibacterial composite conductive ultrafiltration membrane is prepared by an immersion phase inversion method.

2. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 1, characterized in that: In S3, the casting solution includes the following components: N,N-dimethylacetamide (76 wt.%), polyvinylpyrrolidone (5 wt.%) and polyethersulfone (19 wt.%).

3. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 1, characterized in that: In the S1, the addition amount of ethyl orthosilicate is 10-50 mL, the addition amount of 3-aminopropyltriethoxysilane is 0-10 mL, the concentration of sucrose is 0.1-0.9 mol / L, the hydrothermal temperature is 100-200° C., and the sintering temperature of the carbon balls is 500-1000° C.

4. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 1, characterized in that: Tetraethyl orthosilicate ≥98%; Lithium fluoride ≥99%; Hydrochloric acid ≥36%; outer diameter of aminated multi-walled carbon nanotubes: 8-15nm, length: 50μm; n-heptane ≥98%; ammonia water, AR, 25-28%; sucrose is AR grade powder.

5. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 1, characterized in that: In S2, the concentration of the povidone-iodine solution is 1-10 g / L, and the reaction time is 5-20 h.

6. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 1, characterized in that: In S3, the amount of hollow mesoporous carbon nanospheres loaded with antibacterial agents added to the casting solution is 0.1-0.5 g, and the amount of amino-modified multi-walled carbon nanotubes is 0-0.5 g.

7. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 2, characterized in that: In S3, the reaction temperature of the casting solution is 50-100° C., and the reaction time is 1-12 hours.

8. The method for preparing the electrically assisted sustained-release antibacterial conductive ultrafiltration membrane according to claim 2, characterized in that: The polyethersulfone M w =62 kDa, and the polyvinyl pyrrolidone is polyvinyl pyrrolidone K-30.

9. An electrically assisted slow-release antibacterial conductive ultrafiltration membrane, characterized in that: The ultrafiltration membrane is prepared by the method according to any one of claims 1 to 8, wherein the ultrafiltration membrane comprises a matrix, an antibacterial filler and a conductive filler, wherein the matrix is ​​polyethersulfone (PES), and the antibacterial filler is a hollow mesoporous carbon sphere (C PVP-I ), the conductive filler is amino-modified multi-walled carbon nanotubes (CNTs-NH2).

10. Application of electrically assisted slow-release antibacterial conductive ultrafiltration membrane in sewage separation and purification, characterized in that: The method is prepared by the method as claimed in claims 1 to 8.